The role of the operating department practitioner on board Role 2 Afloat. Issue 11 (November 2018) - Stables, A; Seal, G; Mercer, S J
The Role 2 Afloat (R2A) is the Royal Navy (RN)'s Damage Control Resuscitation (DCR), including Damage Control Surgery, capability at sea. There are currently three operating department practitioners (ODP) in the deployed team. This article describes the role of the ODP in this team and the training which is required to fulfil this role.